Hsp90 globally targets paused RNA polymerase to regulate gene expression in response to environmental stimuli. - Sawarkar, R.; Sievers, C.; Paro, R. (Cell, 2012)
The molecular chaperone Heat shock protein 90 (Hsp90) promotes the maturation of several important proteins and plays a key role in development, cancer progression, and evolutionary diversification. By mapping chromatin-binding sites of Hsp90 at high resolution across the Drosophila genome, we uncover an unexpected mechanism by which Hsp90 orchestrates cellular physiology. It localizes near promoters of many coding and noncoding genes including microRNAs. Using computational and biochemical analyses, we find that Hsp90 maintains and optimizes RNA polymerase II pausing via stabilization of the negative elongation factor complex (NELF). Inhibition of Hsp90 leads to upregulation of target genes, and Hsp90 is required for maximal activation of paused genes in Drosophila and mammalian cells in response to environmental stimuli. Our findings add a molecular dimension to the chaperone's functionality with wide ramifications into its roles in health, disease, and evolution.